NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL TENTANG KAMU KARYA TERE LIYE - Zulfikarni, Khairina, Erizal Gani, (Universitas Negeri Padang, 2017)
The purpose of this study is to describe the value of character education in the novel Tentang Kamu by Tere Liye. This research data is in the form of words, phrases, sentences, and discourse that displays events and figures that indicate the values of character education contained in Tere Liye's novel Tentang Kamu. The source of this research data is Tere Liye's novel Tentang Kamu. Data are collected by reading and understanding, inventorying, interpreting, classifying and summarizing data relating to the character education values in Tere Liye's novel Tentang Kamu and based on apresiasif reading. The research findings are the value of character education found in the novel Tentang Kamu by Tere Liye as much as 155 data.Â Kata Kunci: nilai, pendidikan, karakter, implikasi